earlyMYCO: assessing the risk associated to early-life exposure to mycotoxins - Assunção, Ricardo (2021)
A number of health disorders has been associated to exposure to hazardous chemicals during the first 1000 days of life. Therefore, a proper risk assessment built on accurate data assumes particular im-portance to evaluate the potential impact that early-life exposure could represent in adulthood. Mycotox-ins are secondary fungal metabolites that might cause harmful effects in humans and animals. Recent studies showed that Portuguese young children are exposed to multiple mycotoxins through food con-sumption which could constitute a health concern. However, earlier exposure to these compounds re-mains unexplored. earlyMYCO – Early-life exposure to MYCOtoxins and its impact on health, a national funded project, intends to contribute to clarify this issue evaluating the health effects of early-life exposure of Portuguese mother-and-child pairs to mycotoxins and assessing the associated risk. The Estimated Daily Intake, using human biomonitoring data, will be compared with reference dose values. For those mycotoxins representing a health concern, an estimate of the associated probable health-impact will be performed by calculating the associated burden in terms of disability-adjusted life years (DALY). Preliminary results of exposure to mycotoxins through food consumption (cereal-based foods) in young children (≤ 3 years old) revealed a potential adverse health effect for percentiles of intake of aflatoxins above or equal to P50 (corresponding to 0.041 ng/kg body weight/day or higher). Our results will contribute to reach an accurate risk assessment framework and to establish and prioritize preventive measures to reduce exposure to chemicals, especially for vulnerable population groups as pregnant women and infants.